MANIFEST INTERTEKSTUALITAS DALAM BERITA AIMAN KOMPAST MENELUSURI JALAN KEMATIAN JANGGAN SANG AKTIVIS - Mu’minin; Ali Nuke Affady Affady (Prodi Pendidikan Bahasa dan Sastra Indonesia IKIP WIDYA DARMA, 2022)
This research is motivated by discourse analysis in three dimensions, namely text, discourse practice, and sociocultural practice. In addition to these three dimensions, there is intertextuality which is part of the text. Intertextuality is divided into manifest intertextuality and interdiscursivity. This intertextuality can be found in the news of Aiman ​​KompasTV Tracing the Way of Janggal's Death of the Activist Episode 14 October 2019. This study aims to determine the intertextuality in the intertextuality manifest in the form of discourse representations, presuppositions, and irony in the news of Aiman ​​KompasTV's Tracing the Janggal Death of the Activist Episode 14 October 2019. This research method uses a qualitative descriptive approach. The data in this study are in the form of words, phrases, and sentences in the news transcript of Aiman ​​KompasTV. Data collection in this study included downloading videos on the official KompasTV Youtube, data transcripts, marking, and coding. The data analysis used by the researcher is to classify the data, analyze the data, and conclude the data from the analysis. The results showed that there were findings in the form of representations of discourse, presuppositions, and irony. The representation of discourse in this study is to find a process of forming meaning in every utterance conveyed by journalists to convince the audience that the reports submitted are in accordance with the actual conditions that occur in the field. The presuppositions in this study are used by journalists to invite sources and listeners to assume the utterances that he conveys. The aim is to strengthen the argument that what journalists convey is a form of truth. Irony in this study is used by journalists to quip the sources. The satire was made by journalists because the statements made by the interviewees were not in accordance with the conditions on the ground